TINJAUAN ATAS PENCATATAN BELANJA BARANG PADA LAPORAN KEUANGAN DI DIREKTORAT JENDERAL TANAMAN PANGAN KEMENTERIAN PERTANIAN - Nabilla Wildaty (2021)
Financial statement prepared for expenditure accounts are financial statement for 2020, in the form of budget Realization Reports, Balance Sheet, and Notes to Financial Statements which refers to Government Regulation Number 71 of 2010 concerning Government Accounting Standarts and sound financial management principles in government. In the financial statements, the expenditure account is certainly one of the major influences for the Directorate General of Food Crops. Because basically ever agency, both private and government, must spend all its needs in each period. Purchases for goods at the Directorate General of Food Crops, Ministry of Agriculture, especilly for ATK spending, will become supplies for the current period.